A contrastive analysis of linguistic features of the adjective “black” in english And “đen” in vietnamese (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This paper is a contrastive analysis of linguistic features of the adjective Black in English and Đen in Vietnamese. For observation and analysis, the data of 300 adjectives Black and 300 adjectives Đen as well as 300 samples collected from British, American and Vietnamese stories, novels, newspapers and idioms books . In fact, in order to make sure that the samples, especially with regard to Vietnamese equivalents being in the validity and reliability, the short stories and novels chosen are from bilingual sources. Further, collected samples from the websites should be in the most similar meaning with the analysis of the data from literary works. To begin with, by taking and analysing various samples, this research aims at finding out semantic similarities and differences as well as the similar and different cases of pragmatics. The main study is then focused on exploitation and contrast of these two adjectives in English and Vietnamese. Eventually, the implications for the teaching and learning of words, translation as well as for further study are put forward.